Code Choice and Meaning of Ganesa Statue in School Area (A Case Study of Linguistics Landscapes) - Ni Made Ayu Sulasmini; Naniana N Benu; I Wayan Mulyawan (e-Journal of Linguistics, 2025)
This article aimed at investigating the presence of Ganesa statue in the school premises, in terms of the code choice and symbolic meaning. The code choice within this article focuses on the language preferences that it used to communicate the meaning, meanwhile meaning refers to the physical, material and its symbolic aspects. This is a qualitative research. The data was obtained from field and library research that further confirmed by an interview with the school authority and priest. It is found that the signage on the statue is written in Balinese Language by using Balinese script and Latin. Ganesa within this school context, indicates the existence of masculine power of knowledge, displaying aesthetic, and keeping the unworthy away, the statues are also symbolizing the existence of Ganesa as a medium for prayin